2011
DOI: 10.3390/e13051034
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Magnetic Field Effect on Entropy Generation at Thermosolutal Convection in a Square Cavity

Abstract: Thermosolutal convection in a square cavity filled with air and submitted to an inclined magnetic field is investigated numerically. The cavity is heated and cooled along the active walls with a mass gradient whereas the two other walls of the cavity are adiabatic and insulated. Entropy generation due to heat and mass transfer, fluid friction and magnetic effect has been determined in transient state for laminar flow by solving numerically the continuity, momentum energy and mass balance equations, using a Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…They found that the structure of the flows inside the cavity depends on four dimensionless parameters such as thermal Grashof number, the inclination angle, the irreversibility distribution ratio and the aspect ratio of the cavity. Further, the effect of the magnetic field on the entropy generation with the thermosolutal convection [23] and the discrete heater at the vertical wall of the cavity [24] is also reported. Current work focuses on the analysis of the entropy generation during natural convection in rhombic enclosures based on inclination angles to meet the requirement of various industrial applications involving the electronic cooling, solar heating, etc.…”
Section: Nomenclaturementioning
confidence: 98%
“…They found that the structure of the flows inside the cavity depends on four dimensionless parameters such as thermal Grashof number, the inclination angle, the irreversibility distribution ratio and the aspect ratio of the cavity. Further, the effect of the magnetic field on the entropy generation with the thermosolutal convection [23] and the discrete heater at the vertical wall of the cavity [24] is also reported. Current work focuses on the analysis of the entropy generation during natural convection in rhombic enclosures based on inclination angles to meet the requirement of various industrial applications involving the electronic cooling, solar heating, etc.…”
Section: Nomenclaturementioning
confidence: 98%
“…in the present work and denote irreversibility distribution ratios related to velocity gradients, concentration gradients, and mixed product of concentration and thermal gradients, respectively (Magherbi et al 2006;Bouabid et al 2011;Ghachem et al 2012).…”
Section:  mentioning
confidence: 99%
“…Jery et al [31] numerically investigated the influence of an inclination angle of the magnetic field on entropy generation in natural convection for air and liquid gallium. Bouabid et al [32] studied the thermosolutal convection in a square cavity filled with a binary gas mixture under an inclined magnetic field. It was found that the magnetic field induced the decrease of entropy generation.…”
Section: Introductionmentioning
confidence: 99%